Research on Strengthen the Development and Utilization of Geospatial Data to Release the Value of Data Elements - H. Li; H. Li; H. Li; H. Li; W. Huang; Y. Xu; W. Zhao; X. Zheng; J. Yang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
As an important basic and strategic information resource of a country, geospatial data is widely used in economic construction, social development, national defense construction and other fields. Geospatial data as an important public data, promote its development and utilization, strengthen the circulation of geospatial data elements, and release the value of geospatial data elements. On the one hand, it is necessary to improve the New Spatial Data Infrastructure (NSDI), and strengthen the sharing and opening of geographic information data. On the other hand, it is necessary to deepen the application and innovation of geospatial data to enhance the security of geospatial data. Firstly, this paper gives the definition and connotation of circulation mode of geospatial data elements. Secondly, the basic requirements, technical indicators and overall architecture of circulation portal of geospatial data elements are designed, including basic operation environment configuration, construction under the scene of the Geospatial Data Exchange Mode (GDEM)/ Geospatial Data Opening Mode (GDOM)/ Geospatial Data Trading Mode (GDTM)/ Geospatial Data Sharing Mode (GDSM). Finally, the challenges and opportunities faced by the circulation of geospatial data elements were summarized, mainly focusing on construction of the NSDI and geospatial data circulation security governance.